Antenna array beamforming and measurement using a digital storage scope - Phua, Vivien Hui Chin (2015)
Antenna array beamforming is very useful in today’s wireless communications. Without it, there will be many limitations in wireless communications. In this project, the proof of concept of basic antenna array beamforming will be done with the help of a digital storage oscilloscope. First of all, the use of the Universal Software Radio Peripheral (USRP) X310 and its software component, GNU Radio, will be introduced in Chapter 2. The USRP X310 is capable of simulating a simple baseband signal and they both play a part in transmitting and receiving signals wirelessly through antennas. Limitations of using the USRP X310 and GNU Radio will be further discussed in the chapter. In Chapter 3, the generation and usage of ultra wideband (UWB) signal will be reviewed. This chapter involves heavy usage of Matlab software in order to create a suitable UWB signal as the antennas used are narrowband. The UWB signal is created for transmission between antennas. However, this also gives rise to many limitations which will be further elaborated. The next chapter replaces the UWB signal with the time-limited cosine signal. Antenna arrays are set up with matched and unmatched orientations. The different received signals are shown. This chapter also discusses noise and its effects on signal transmission and the possible limitations that could not be avoided in this project. As the antenna efficiency is very low, amplifiers are added in and the project is conducted in an anechoic chamber to minimize radio frequency (RF) interferences. Lastly, the project is concluded and possible research works are recommended for future study.